Tanggung Jawab Hukum Perusahaan Ekspedisi Atas Hilangnya Barang Konsumen - Meiliana Kamila; Imam Haryanto (Jurnal USM Law Review)
This study aims to examine the loss of consumer goods caused by freight forwarding companies, which causes consumers to suffer losses due to negligence of shipping company services. To protect consumer rights that must be fulfilled. The method used is normative juridical by carrying out legal research on literature which is carried out by examining library materials or secondary data solely on research and the laws that regulate it. Regarding the discussion, this research shows legal remedies for the loss of consumer goods caused by shipping companies, legal consequences received by shipping company services, and forms of consumer protection for rights that are not fulfilled. This study concludes that legal remedies can be used to resolve disputes, which can be resolved in 2 ways, namely through the court and outside the court by arbitration, mediation, and conciliation. The results of this study aim to update previous studies to examine more deeply related to the protection of various consumer rights that are not fulfilled due to the negligence of shipping companies. As well as solutions so that consumer losses that arise do not continue to occur.